Enhancing the Institutional Model for District Heating Regulation : Outside Perspectives and Suggestions - World Bank (Washington, DC, 2014)
Chapter one introduces the paper and briefly summarizes the main reform objectives and issues for District Heating (DH) in China. Chapter two presents relevant alternatives and lessons learned on approaches to regulatory practices in district heating internationally. Chapter three presents key findings and options for enhancing the institutional framework for DH regulation. Several Annexes complement the chapters by focusing especially on special topics raised by the MOHURD during this technical assistance activity. Annex one elaborates on chapter one, providing an overview of the current situation in China. Annex two introduces options for monitoring and benchmarking. Annex three discusses various methods for cost allocation of Combined Heat and Power (CHP). Annexes four, five, and six complements aspect of analysis on pricing and equity issues, a summary of options for competition among DH suppliers, and an example of red line impediments to energy efficiency innovation.